2011
DOI: 10.1186/1476-7120-9-10
|View full text |Cite
|
Sign up to set email alerts
|

Target heart rate to determine the normal value of coronary flow reserve during dobutamine stress echocardiography

Abstract: BackgroundThe determination of coronary flow reserve (CFR) is an essential concept at the moment of decision-making in ischemic heart disease. There are several direct and indirect tests to evaluate this parameter. In this sense, dobutamine stress echocardiography is one of the pharmacological method most commonly used worldwide. It has been previously demonstrated that CFR can be determined by this technique. Despite our wide experience with dobutamine stress echocardiography, we ignored the necessary heart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 28 publications
1
21
0
3
Order By: Relevance
“…7 At present, the possibility of determining mean distal flow in the LAD and its CFVR exceeds 95% of patients evaluated. 21,24,25 The CFVR information is additive to the exclusive wall motion result, as confirmed in a meta-analysis performed of five studies by Rigo, 10 which included our experience, 11 showing an increase in diagnostic sensitivity (from 67 6 9% to 90 6 3%) with scarce loss of specificity (from 93 6 2% to 86 6 12%) and remarkable increase in test accuracy (from 79 6 5% to 89 6 7%). Yet the prognostic value of CFVR has been explored in depth only in recent years.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…7 At present, the possibility of determining mean distal flow in the LAD and its CFVR exceeds 95% of patients evaluated. 21,24,25 The CFVR information is additive to the exclusive wall motion result, as confirmed in a meta-analysis performed of five studies by Rigo, 10 which included our experience, 11 showing an increase in diagnostic sensitivity (from 67 6 9% to 90 6 3%) with scarce loss of specificity (from 93 6 2% to 86 6 12%) and remarkable increase in test accuracy (from 79 6 5% to 89 6 7%). Yet the prognostic value of CFVR has been explored in depth only in recent years.…”
Section: Discussionsupporting
confidence: 63%
“…21 In the present study, 53.9% of patients were assessed under dobutamine (351 of 651), with a feasibility of 90%, slightly lower than that with dipyridamole. The results showed that dobutamine was as efficient as dipyridamole to predict events, without significant differences between the two stress agents (Figure 4).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…13. It is extremely important to reach a delta heart rate of at least 50 bpm or a heart rate of at least 75% of the maximum predicted heart rate to consider a CFR value abnormal [36].…”
Section: Coronary Flow Reserve During Dobutamine Stress Echocardiographymentioning
confidence: 99%
“…Some studies reported that heart rate and blood pressure can impact CFR. 43 Further research is required to investigate whether FTY720 has an impact on the heart rate of diabetic rats.…”
Section: Study Limitationsmentioning
confidence: 99%